Post-Secondary Student Belonging in a Virtual Learning Environment During COVID-19 - Smith, Nadine; Graham, Jan Marie; Waddell-Henowitch, Candice; De Moissac, Danielle; Lam, Michelle (Canadian Journal of Higher Education, 2023)
Psychological and social adjustment and academic success in post-secondary institutions are supported by a sense of belonging to a social group and having meaningful relationships with other students, staff, and faculty members. This exploratory study used a qualitative approach to investigate post-secondary students’ sense of belonging in the virtual learning environment during the COVID-19 pandemic. The study was conducted at a small Western Canadian university. Semi-structured interviews were conducted with 20 participants who were undergraduate students, from various faculties, and in different years in their programs. Findings were clustered into three themes: (1) student expectations of university, (2) impact of virtual learning environments on students, and (3) the role of educators. Recommendations are included to enhance support and belonging for post-secondary students in virtual learning environments.